Factors Influenced the Quality of Sleep among Patients with Coronary Artery Bypass Graph: A Literature Review - Hermin Esti Dianingtyas; Agung Waluyo (International Journal of Nursing and Health Services (IJNHS), 2020)
Coronary heart disease is a condition of narrowing the coronary artery lumen due to fat accumulation, which causes reduced blood flow. One of the interventions to overcome the blockage is surgical coronary artery bypass graft (CABG). CABG can help patients overcome obstructions in the coronary arteries. However, CABG can cause disturbances in sleep patterns that can reduce the quality of life of patients. The purpose of this paper is to find out what factors influence sleep quality in post CABG patients. This paper is a literature study of several databases in ELSEVIER, PROQUEST, EBSCO, PMC, JMH, JMC. The result found that sleep quality in post CABG patients was influenced by age, sex, emotional distress, the effect of treatment, surgery, and comorbidity, and environmental factors. Nurses need to improve their ability to conduct sleep quality assessments in patients after CABG patients using the international sleep quality assessment format